The kinetics of multibranch integration on the dendritic arbor of CA1 pyramidal neurons - Yang, Sunggu; Emiliani, Valentina; Tang, Cha-Min (Frontiers in Cellular Neuroscience, 2014)
The process by which synaptic inputs separated in time and space are integrated by the dendritic arbor to produce a sequence of action potentials is among the most fundamental signal transformations that takes place within the central nervous system. Some aspects of this complex process, such as integration at the level of individual dendritic branches, have been extensively studied. But other aspects, such as how inputs from multiple branches are combined, and the kinetics of that integration have not been systematically examined. Using a 3D digital holographic photolysis technique to overcome the challenges posed by the complexities of the 3D anatomy of the dendritic arbor of CA1 pyramidal neurons for conventional photolysis, we show that integration on a single dendrite is fundamentally different from that on multiple dendrites. Multibranch integration occurring at oblique and basal dendrites allows somatic action potential firing of the cell to faithfully follow the driving stimuli over a significantly wider frequency range than what is possible with single branch integration. However, multibranch integration requires greater input strength to drive the somatic action potentials. This tradeoff between sensitivity and kinetics may explain the puzzling report of the predominance of multibranch, rather than single branch, integration from in vivo recordings during presentation of visual stimuli.